Pembelajaran Pendidikan Karakter Peduli Lingkungan Melalui Program Adiwiyata di SDN Bunulrejo 2 Kota Malang - Martha, Martha Setyaningati; Akbar, Sa’dun; Mahanani, Putri (Universitas Nusantara PGRI Kediri, 2020)
Abstract: Learning environmental character education is a process of organizing the environment around students in the learning prosess that can be done inside and outside classroom. The purpose of this research is to describe the implementation of the Adiwiyata program and environmental care characters that appear to have been carried out by students as well as the role of the Adiwiyata program in learning environmental chacarter education at SDN Bunulrejo 2 Malang City. This research use qualitative descriptive approach. Sources of data in this research are the principal, teachers, and students. Data collection tehniques carried out by observation, interviews, and documentation. Data analysis of the research carried out by data reduction, data presentation, and conclusion recall. The results showed that the role of the Adiwiyata program in learning character education at SDN Bunulrejo 2 Malang City can develop the character of protecting the environment, cooperation, responsibility, and discipline in the school environment. The implementation of the Adiwiyata program at SDN Bunulrejo 2 Malang City was carried out using four components: (1) School policies with an environmental perspective, (2) Implementation of an environment-based curriculum, (3) Participatory based environmental activities, (4) Management of environmentally friendly. Chacarter cares the environment that looks conducted by students at SDN Bunulrejo 2 Malang City is to protect environment, cooperation, responsibility, and discipline.